Answer: n = 7
Step-by-step explanation; Simplifying
6n + -7 = 14 + 3n
Reorder the terms:
-7 + 6n = 14 + 3n
Solving
-7 + 6n = 14 + 3n
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '-3n' to each side of the equation.
-7 + 6n + -3n = 14 + 3n + -3n
Combine like terms: 6n + -3n = 3n
-7 + 3n = 14 + 3n + -3n
Combine like terms: 3n + -3n = 0
-7 + 3n = 14 + 0
-7 + 3n = 14
Add '7' to each side of the equation.
-7 + 7 + 3n = 14 + 7
Combine like terms: -7 + 7 = 0
0 + 3n = 14 + 7
3n = 14 + 7
Combine like terms: 14 + 7 = 21
3n = 21
Divide each side by '3'.
n = 7
Simplifying
n = 7